2023
DOI: 10.3390/jcm12082983
|View full text |Cite
|
Sign up to set email alerts
|

Novel Time-Lapse Parameters Correlate with Embryo Ploidy and Suggest an Improvement in Non-Invasive Embryo Selection

Abstract: Selecting the best embryo for transfer is key to success in assisted reproduction. The use of algorithms or artificial intelligence can already predict blastulation or implantation with good results. However, ploidy predictions still rely on invasive techniques. Embryologists are still essential, and improving their evaluation tools can enhance clinical outcomes. This study analyzed 374 blastocysts from preimplantation genetic testing cycles. Embryos were cultured in time-lapse incubators and tested for aneupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Conversely, an excessively rapid development can result in disorderly or abnormal divisions [28]. Recent time-lapse microscopy stud-ies have found that kinetic markers of too-slow and too-fast blastocyst formation were related to aneuploid embryos [29][30][31]. This study was designed similar to using time-lapse microscopy to predict euploidy but suggests a more cost-effective and simple method.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an excessively rapid development can result in disorderly or abnormal divisions [28]. Recent time-lapse microscopy stud-ies have found that kinetic markers of too-slow and too-fast blastocyst formation were related to aneuploid embryos [29][30][31]. This study was designed similar to using time-lapse microscopy to predict euploidy but suggests a more cost-effective and simple method.…”
Section: Discussionmentioning
confidence: 99%